1983
DOI: 10.1002/1097-0142(19830515)51:10<1838::aid-cncr2820511014>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Intramammary lymph nodes

Abstract: Radiographic, gross, and histopathologic studies on 158 whole breasts with primary operable carcinoma revealed intramammary lymph nodes in 28%, and of these breasts, 10% contained a metastatic deposit of carcinoma. Cancerous and noncancerous nodes were found in all quadrants of the breast with the positive ones being in the same quadrant as the carcinoma only 50% of the time. There was no demonstrable connection with the usual lymphatic drainage of the breast. With Stage II carcinoma, positive intramammary lym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
1
5

Year Published

1997
1997
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 3 publications
0
42
1
5
Order By: Relevance
“…[57][58][59] Low-lying axillary lymph nodes or deep pectoral lymph nodes can be mistaken for IMLNs. IMLNs are a potential site for the regional spread of breast cancer.…”
Section: Preoperative Identification and Detection Of Metastatic Tumomentioning
confidence: 99%
“…[57][58][59] Low-lying axillary lymph nodes or deep pectoral lymph nodes can be mistaken for IMLNs. IMLNs are a potential site for the regional spread of breast cancer.…”
Section: Preoperative Identification and Detection Of Metastatic Tumomentioning
confidence: 99%
“…On the other hand, among the surgical breast specimens, the rate of intramammary lymph node identifi cation in the community hospital and university hospital was 0.83% and 1.6%, respectively; however, according to a more detailed examination based on mammography of the entire breast specimen, at least one intramammary node was found in 28% of the specimens. 12 A prospective study of 1500 consecutive screening mammograms showed small nodules of <15 mm in 13.3% of all cases, and 81 (5.4%) had 1-3 upper outer quadrant nodules with the characteristics of benign intramammary lymph nodes. 13 It has been suggested that intramammary lymph node status could indicate an intermediary phase between Stage I and II breast carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Intramammary lymph nodes are the most common cause of nonpathological masses seen on conventional mammography, being detected in about 30% of breasts, mostly in the upper-outer quadrants [1]. The typical mammographic features of intramammary lymph nodes (size smaller than 15 mm, round or oval shape, regular margins, low density, association with a vascular branch and, frequently, a radiolucent centre) have been clearly established [1][2][3][4][5][6][7], and their detection does not warrant further diagnostic investigation Introduzione I linfonodi intra-mammari costituiscono la causa più frequente di formazione espansiva con significato non patologico riscontrata all'esame mammografico convenzionale: sono infatti presenti in circa il 30% delle mammelle, prevalentemente nei quadranti supero-esterni [1].…”
Section: Introductionmentioning
confidence: 99%
“…The typical mammographic features of intramammary lymph nodes (size smaller than 15 mm, round or oval shape, regular margins, low density, association with a vascular branch and, frequently, a radiolucent centre) have been clearly established [1][2][3][4][5][6][7], and their detection does not warrant further diagnostic investigation Introduzione I linfonodi intra-mammari costituiscono la causa più frequente di formazione espansiva con significato non patologico riscontrata all'esame mammografico convenzionale: sono infatti presenti in circa il 30% delle mammelle, prevalentemente nei quadranti supero-esterni [1]. I caratteri mammografici tipici dei linfonodi intra-mammari (dimensioni inferiori a 15 mm, morfologia rotondeggiante od ovalare, contorni regolari, bassa densità, associazione con una diramazione vascolare e frequente area centrale di maggiore radio-trasparenza) sono chiaramente codificati da lungo tempo in letteratura [1][2][3][4][5][6][7] ed il unless enlargement of the mass is seen on a subsequent mammographic examination [8][9][10][11][12][13]. However, in rare cases, breast cancers may exhibit mammographic features compatible with intramammary lymph nodes [1,2,9,11].…”
Section: Introductionunclassified